1959
DOI: 10.1128/jb.77.3.361-366.1959
|View full text |Cite
|
Sign up to set email alerts
|

Growth Studies and Plate Counting of Leptospires

Abstract: The earliest report of the cultivation in vitro of pathogenic leptospires is that of Inada et al. (1916). From 1916 until the present, various media, both liquid and semisolid, have been developed and used for research and diagnostic purposes. Examples of such media are those of Korthof (1932), Chang (1947), Stuart (1946), and Cox (1955). A common denominator for growth of leptospires which is present in all of the media is some type of body fluid such as serum, whole blood, or ascites fluid. The literature co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…2 Studies have evaluated the use of plate counts to determine colony-forming units, but this technique requires a long incubation period, from 12-14 days. 3 In addition, counts obtained through the pour-plate technique represent viable count, which may be different from the total count derived from dark-field microscopy or the Coulter counter. Additionally, there are methods for indirect quantification, measuring the turbidity of the culture media.…”
Section: Discussionmentioning
confidence: 99%
“…2 Studies have evaluated the use of plate counts to determine colony-forming units, but this technique requires a long incubation period, from 12-14 days. 3 In addition, counts obtained through the pour-plate technique represent viable count, which may be different from the total count derived from dark-field microscopy or the Coulter counter. Additionally, there are methods for indirect quantification, measuring the turbidity of the culture media.…”
Section: Discussionmentioning
confidence: 99%
“…VOL. 13,1981 able to correlate any identifying physiological characteristic with the ability to form surface colonies. The cells of these two colonial types probably differ in their oxygen requirements or their ability to penetrate the agar.…”
Section: Fig 2 Surface Coloniesmentioning
confidence: 99%
“…Subsequently, numerous reports on the colonial growth of leptospires were published (7, 8, 14-16, 18, 19). Larson et al (13) demonstrated that leptospiral colonies were derived from the growth of single cells. It was observed that a sequential change in colonial morphology may occur as the colonies mature (16) and that colonial heterogeneity exists in some serovars of Leptospira (14,16).…”
mentioning
confidence: 99%
“…Colonization of Leptospira was first reported in 1957 by Cox and Larson (2). There is only one known report of the use of this counting procedure for describing growth (4) and there are no reports of its application to survival studies. According to Bodily et al (1), not all serotypes of Leptospira will colonize, and results between laboratories have not always been reproducible.…”
mentioning
confidence: 99%